Bash scripting fundamentals : LiveLessons - Vugt, Sander van; Safari eBooks ([Place of publication not identified] : Prentice Hall : Pearson, 2016)
"Bash Scripting Complete Video Course teaches you everything you need to know about shell scripting, from novice scripting to advanced script analysis and scripting for performance. This course consists of 16 lessons that take you from learning Bash basics to advanced scripting concepts. Each lesson contains practical examples to show how scripting solutions are being used in the real world. Each lesson concludes with an exercise, so you can test your own skills. A video explanation is also included so you can follow along and check your work. You will end the course by going beyond Bash and starting your first Python project."--Resource description page.
Presenter, Sander van Vugt.
Title from title screen (viewed July 5, 2016).
Keywords: Linux; Computer programming; Electronic books